Epidemiological study of open fractures of the ankle and foot - Carneiro, Leandro Pessoa; Gonzaga Filho, Luiz Augusto Sampaio; Mizusaki, Jorge; Prata, Sergio; Rizzo, Marco (Journal of the Foot & Ankle, 2021)
Objective: To characterize the epidemiological profile of patients treated at a hospital service with diagnosis of open fracture of the ankle and foot. Methods: Retrospective, descriptive, epidemiological, observational study of open fractures of the ankle and foot selected by convenience sampling in a hospital service in São Paulo, state of São Paulo, Brazil, from March 1, 2017, to March 1, 2019, totaling 109 patients. Data collection was conducted for the analysis of variables included in patients’ medical records. Results: The medical records of 700 patients with open fractures were assessed. Of these patients, 13.2% (109 patients) had open fractures of the ankle and foot. There was a predominance of male young adults (70.8%) and of left lower limb fractures (51.85%). Most cases were classified as Gustilo and Anderson type II fractures (42.6%). Motorcycle accidents (44.45%) predominated, and students and professional motorcyclists were the most frequent occupations (37.04%). The most adopted stabilization method was osteosynthesis (internal fixation) (44.45%), and primary amputation was required in 3.7% of the cases. Conclusion: Male young adults were the most affected by fractures of the ankle and foot, and traffic accidents were the leading cause. Most patients had an educational attainment of complete elementary education. Most fractures were classified as Gustilo and Anderson type II. Greater severity was observed in patients with associated injuries in other body segments and who developed early complications during hospitalization. Level of Evidence IV; Prognostic Studies; Case Series.